Coherence and Gap Between Service Quality Attributes and Customer Satisfaction - Ihsan Nurhadi; Bambang Darmawan (Universitas Pendidikan Indonesia, 2022)
Service conformance to customer expectations is measured in terms of service quality. In order to enhance their services, spot issues as they arise, and more accurately gauge customer satisfaction, service business owners frequently evaluate the quality of the services they offer to their clients. The link between sustainable product qualities and consumer decision-making has been the subject of significant research advancements in recent decades. Nonetheless, despite the substantial quantity of research, conclusions are still dispersed and occasionally even inconsistent. Because customers' assessments of service quality vary widely, the goal of this study is to demonstrate analytically and empirically how the SERVQUAL dimensions are coherent across service industries and even within the same service industry. Because the five SERVQUAL dimensions do not correspond to a customer's psychometric aspects of service quality, this conclusion suggests that there is a gap and lack of coherence between SERVQUAL's five dimensions and customer satisfaction.